2013
DOI: 10.1007/s13555-013-0034-x
|View full text |Cite
|
Sign up to set email alerts
|

Vulval Crohn’s Disease in Childhood

Abstract: Vulval involvement in Crohn’s disease (CD) is rare, particularly in children. The clinical features include erythema, edema, ulceration, and labial skin tags. The authors present two cases of children with vulval CD. In both cases, marked labial edema was the presenting feature. In one patient the immunomodulator tacrolimus ointment 0.03% was used with success. In the second patient control was achieved with intralesional triamcinolone in combination with systemic metronidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Vulvar biopsy reveals chronic inflammatory changes with noncaseating granulomatous inflammation. Differential diagnoses to consider include cellulitis, pyogenic infections, hidradenitis suppurativa, sarcoidosis, tuberculosis, foreign body reactions, contact dermatitis, acquired lymphangiectasia, and sexual abuse . Metastatic Crohn's disease in children is rare—a literature review in 2009 found 28 individual case reports spanning 40 years, with genital Crohn's disease accounting for 21 of the 28 cases .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Vulvar biopsy reveals chronic inflammatory changes with noncaseating granulomatous inflammation. Differential diagnoses to consider include cellulitis, pyogenic infections, hidradenitis suppurativa, sarcoidosis, tuberculosis, foreign body reactions, contact dermatitis, acquired lymphangiectasia, and sexual abuse . Metastatic Crohn's disease in children is rare—a literature review in 2009 found 28 individual case reports spanning 40 years, with genital Crohn's disease accounting for 21 of the 28 cases .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of optimal management is limited and usually involves medical management of underlying Crohn's disease. Regimens used include metronidazole, azathioprine, methotrexate, oral and topical steroids, and tumor necrosis factor‐alpha inhibitors such as infliximab and adalimumab . Other agents such as 6‐mercaptopurine, sulfasalazine, and ciclosporin have also been used .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations